Sustainable approach to alternative raw materials in the inorganic coating industry: Chromite mining process waste as MgO and SiO2 source - Karaman-Unluturk, Kumru; Yilmaz, Yasin Bozkurt; Karaahmet, Oguz; Cicek, Buga (ELSEVIER, 2025)
The evaluation of waste's economic value and increased reusability in industry offers environmental and economic benefits. This study investigates using chromite ore processing residue (COPR) in sodium borosilicate glass-ceramic coatings (GCC) to mitigate potentially hazardous components like Cr6+. Precursor glass (PG) production, a crucial step in GCC production, involves high temperatures. TG-DTA analysis and subsequent calcination of COPR at critical temperature points were conducted. Analysis of calcined samples examined composition, phases, microstructures, and surface areas, guided by TG-DTA results. The study identified reaction points and phase transformations correlated with temperature changes. Low-temperature calcination yielded Chrysotile and Lizardite phases, transitioning to Forsterite and enstatite at higher temperatures. PGs melted at 1300 degrees C revealed chemical composition changes and amorphous structures. GCCs applied to steel surfaces exhibited favorable microstructural evaluations, with fluoro-tremolite and quartz as main phases. XPS analysis confirmed the immobilization and transformation of Cr6+ to Cr3+ in the glass structure. This research demonstrates COPR's successful utilization as a raw material, ensuring environmental safety and economic viability in industrial processes.
Keywords: COPR; Chromite; Cr 6+reduction; Characterization; Sustainable raw material; GLASS-CERAMICS; PHASE-TRANSFORMATION; RAMAN; RESIDUE; CRYSTALLIZATION; IMMOBILIZATION; PRESSURE; CALCIUM; CRISTOBALITE; ANTIGORITE; Chemistry